Performance of cassava (Manihot esculenta Crantz) based cropping systems and associated soil quality changes in the degraded tropical uplands of East Java, Indonesia - Islami, Titiek; Guritno, Bambang; Utomo, Wani Hadi (Journal of Tropical Agriculture, 2011)
Field studies were conducted (2005 to 2009) in the degraded uplands (Entisols) of East Java, Indonesia to evolve a sustainable cassava (Manihot esculenta Crantz) production technology. Screening of crops and cropping systems for profitability was followed by standardization of soil management techniques to optimize productivity. The screening trials indicated that cassava – either as sole crop or under intercropping systems – is a profitable crop for this region. Application of inorganic fertilizers, however, failed to sustain cassava productivity. Sole cassava yield was 9.9 Mg ha–1 during the first year, which decreased to 7.44 Mg ha–1 in the fourth year. Supplementing inorganic fertilizers with organic manures, either through farmyard manure or through addition of residues of the intercrops, was beneficial to maintain cassava productivity and soil quality. Intercropping cassava with peanuts (Arachis hypogaea L.) and cowpea (Vigna unguiculata (L.) Walp) was particularly useful. Sole cassava treated with 7.5 Mg ha–1 FYM produced a stable tuber yield of about 13 Mg ha–1 and cassava intercropped with peanut and cowpea gave yields of about 16 Mg ha–1, implying complementraty effects of legume intercropping.